Developing Science E-Module Based on Mangrove Ecotourism Project to Foster Scientific Creativity in Islamic Higher Education - Ramdhani Sucilestari; Agus Ramdani; S. Susilawati; Aa Sukarso; Joni Rokhmat; Rendi Restiana Sukardi (Jurnal Pendidikan Islam, 2025)
This study aimed to develop a science e-module based on a mangrove ecotourism project that is feasible, practical, and effective in increasing student scientific creativity in Islamic higher education. This study used the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The e-module is designed by integrating interactive technology-based environmental learning materials. Data were collected through questionnaires, observations, tests, and interviews to assess the feasibility, practicality, and effectiveness of a science e-module developed as part of a mangrove ecotourism project to improve students' scientific creativity. The finding showed that the science e-module based on the mangrove ecotourism project was feasible, practical, and effective in enhancing students' scientific creativity. The validation results of the science e-module based on the mangrove ecotourism project were 96.25% included in the category of “very feasible to use”. The results of the e-module evaluation showed that most respondents gave a positive assessment. The results of the effectiveness test showed that the use of this e-module significantly improved students' scientific creativity (p = 0.00). This is because the use of e-modules can develop students’ critical thinking, problem-solving, and creativity in solving environmental problems. This study advocates for the incorporation of electronic modules into the science education curriculum at universities, recognizing their potential to serve as innovative tools supporting the enhancement of students’ scientific creativity within the realms of environmental education and technological applications.